2008
DOI: 10.1071/fp08104
|View full text |Cite
|
Sign up to set email alerts
|

Thermal acclimation of respiration but not photosynthesis in Pinus radiata

Abstract: Pinus radiata L. were grown in climate-controlled cabinets under three night/day temperature treatments, and transferred between treatments to mimic changes in growth temperature. The objective was to determine the extent to which dark respiration and photosynthesis in pre-existing and new needles acclimate to changes in growth temperatures. We also assessed whether needle nitrogen influenced the potential for photosynthetic and respiratory acclimation, and further assessed if short-term (instantaneous, measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 56 publications
5
27
1
Order By: Relevance
“…For example, we found the highest discrimination in the Apple tree shortly after bud burst, which somewhat resembles the high discrimination reported for aquatic systems shortly after spring bloom (Luz and Barkan, 2011). These findings are in agreement with findings of increased AOX activity shortly after changes in environmental conditions, or before an increase in the rates of respiration through the COX (Moore et al, 2002;Rachmilevitch et al, 2007). As noted above, the AOX is also reported to be activated as a response to stress.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, we found the highest discrimination in the Apple tree shortly after bud burst, which somewhat resembles the high discrimination reported for aquatic systems shortly after spring bloom (Luz and Barkan, 2011). These findings are in agreement with findings of increased AOX activity shortly after changes in environmental conditions, or before an increase in the rates of respiration through the COX (Moore et al, 2002;Rachmilevitch et al, 2007). As noted above, the AOX is also reported to be activated as a response to stress.…”
Section: Discussionsupporting
confidence: 81%
“…To the best of our knowledge, this study is the only one to date that has estimated AOX activity in intact plants in the field. Given the known relation between AOX and various types of stress (Vanlerberghe and McIntosh, 1997;Moore et al, 2002;Rachmilevitch et al, 2007), working with intact plants has a clear advantage over incubating desiccated plant tissue (Ow et al, 2008;Searle and Turnbull, 2011) that might exhibit a wound response. Using the approach demonstrated here, it is possible to trace how the AOX contribution in woody tissue of a single plant changes seasonally, and due to environmental conditions such as temperature and soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been reported for some conifer and deciduous tree species (Medlyn et al ., ; Hikosaka et al ., ; Ghannoum et al ., ; Gunderson et al ., ), but most studies have shown no acclimatization of photosynthesis to temperature (e.g. Ow et al ., ,b). Our observations indicated that a constant temperature increase of 3°C did not have a significant effect on A net in P. taeda or Q. rubra , compared with A net at ambient temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Hypometabolism as an acclimating effect may be a fundamental aspect of thermal plasticity, and it should be considered when constructing animal energy budgets in the context of GCC. It may also be a universal response by organisms to prolonged shifts in temperature as it has been documented in a broad range of taxa (plants: Ow et al, 2008a;Ow et al, 2008b;fungi: Malcolm et al 2008;crustaceans: Powell and Watts, 2006;insects: Lachenicht et al 2010;fishes: Donelson et al 2011, Strobel et al 2012amphibians: Seebacher and Grigaltchik, 2014;reptiles: this study;birds: Abdelqader and Al-Fataftah, 2014;mammals: Geiser et al 2003). However, these studies did not control for variation in energy intake or food availability, which can covary with climatic temperature shifts (Both and Visser, 2005;Altermatt, 2010;Pearce-Higgins et al, 2010;Allan et al, 2013;Cahill et al, 2013).…”
Section: Thermal Acclimation: Shifts In Metabolism and Behaviormentioning
confidence: 93%